1976
DOI: 10.1017/s0022029900016009
|View full text |Cite
|
Sign up to set email alerts
|

Serological studies on heat-induced interactions of α-lactalbumin and milk proteins

Abstract: The heat denaturation of a-lactalbumin (a-la) in NaCl and KC1 solutions, milk ultrafiltrate and milk was studied using the method of micro complement fixation. It was established that this protein was very resistant to heat denaturation and that it was more stable in milk ultrafiltrate than in the other media studied at temperatures up to 70 °C. Of the various milk proteins added to a-la, only /?-lactoglobulin (/?-lg) formed a heat-induced complex with this protein. This complex was identical in milk ultrafilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
16

Year Published

1981
1981
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 14 publications
0
17
0
16
Order By: Relevance
“…La diminution de la Tm de la~-Lg en présence d'a-La peut s'expliquer par des interactions entre ces 2 protéines. Leur existence est d'ailleurs aujourd'hui bien établie (Hunziker et Tarassuk, 1965;Baer et al, 1976;Elfagm et Wheelock, 1978;Melo et Hansen, 1978). Bien que la nature de ces interactions soit loin d'être élucidée, la participation de ponts disulfures résultant d'échanges SH (de la~-Lg) et SS (de l'a-La) à pH alcalin est très probable.…”
Section: Influence De L'a-launclassified
“…La diminution de la Tm de la~-Lg en présence d'a-La peut s'expliquer par des interactions entre ces 2 protéines. Leur existence est d'ailleurs aujourd'hui bien établie (Hunziker et Tarassuk, 1965;Baer et al, 1976;Elfagm et Wheelock, 1978;Melo et Hansen, 1978). Bien que la nature de ces interactions soit loin d'être élucidée, la participation de ponts disulfures résultant d'échanges SH (de la~-Lg) et SS (de l'a-La) à pH alcalin est très probable.…”
Section: Influence De L'a-launclassified
“…Since whey proteins are a heterogenous group of proteins, it is likely that the gelation behaviour of any individual protein would be altered by the presence of the others. A number of studies have shown that soluble aggregates of whey proteins are formed during the early stages of heat-induced gel formation, and that subsequent polymerization results in the formation of a rigid gel network (Baer et al 1976). It is possible that gel properties may be influenced by the formation of specific soluble aggregates between different whey proteins in the early stages of heating.…”
mentioning
confidence: 99%
“…In the first, the extent of denaturation is measured at the temperature of the experiment, as in the optical rotation studies of Hiraoka et al (1980) or the differential scanning calorimetry of Ruegg et al (1977a, b) and Pfeil (1981). In the second type, the protein solution is heated to a set temperature for a known length of time, cooled, and the extent of denaturation then measured in various ways, (Lyster, 1970;Baer et al 1976;Hillier, 1976;Levieux, 1980). Experiments of the first type have shown that heat denaturation is 80-90% reversible (Riiegg et al 1977a), whereas those of the second type are capable of measuring only the extent of irreversible denaturation.…”
mentioning
confidence: 99%